1998
DOI: 10.1046/j.1365-2133.1998.02465.x
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized, comparative trial of itraconazole versus terbinafine for 2 weeks in tinea capitis

Abstract: In this randomized, double-blind study, the efficacy and safety of oral itraconazole (n = 28) and terbinafine (n = 27), each given for 2 weeks, was compared in patients with tinea capitis. Trichophyton violaceum was the major pathogen in both groups (82.1% and 88.9%, respectively). The final evaluation at week 12 showed a cure rate of 85.7% and 77.8%, respectively (P > 0.05). Adverse events noted were mild and did not warrant discontinuation of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 11 publications
2
37
0
1
Order By: Relevance
“…Terbinafine has already demonstrated its efficacy against the Trichophyton spp. responsible for endothrix infections [2, 3, 4]. It is available in tablets of 250 mg.…”
Section: Methodsmentioning
confidence: 99%
“…Terbinafine has already demonstrated its efficacy against the Trichophyton spp. responsible for endothrix infections [2, 3, 4]. It is available in tablets of 250 mg.…”
Section: Methodsmentioning
confidence: 99%
“…A study has found terbinafine for 2 weeks to be superior in treating T. tonsurans when compared to 2 weeks of itraconazole (91.1 vs 80%) [50], while in another study, 2 weeks of itraconazole was found to be superior in treating T. violaceum than 2 weeks of terbinafine [51]. However, these studies are small and there are no large clinical trials published until this date to compare these two agents, making it inappropriate to conclude.…”
Section: Itraconazolementioning
confidence: 99%
“…The regimen of itraconazole 5 mg/kg/day for 4 weeks appears to be an effective way of treating tinea capitis due to endothrix infections. More recently, high cure rates have also been reported with itraconazole 5 mg/kg/day administered for 2 weeks in endothrix tinea capitis [14]. Itraconazole is also effective against tinea capitis due to M. canis (table 1).…”
Section: Discussionmentioning
confidence: 92%
“…Continuous therapy with itraconazole has been used in various regimens to manage tinea capitis [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14]. Over time there has been a trend to decrease the duration of active therapy while trying to maintain high cure rates [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation